THE EFFECT OF COMPANY'S ROA AND SIZE ON ZAKAT IN SHARIA COMMERCIAL BANKS (International Conference on Social and Islamic Studies, 2021)
The economy in Indonesia is growing rapidly, including the increasing banking sector. Sharia banking must fulfill all economic orders that have been set out in the Qur'an and Hadith including obeying the pillars of faith and the pillars of Islam. One of the five pillars of Islam that must be implemented is Zakat. According to Islamic law, zakat is an asset that is issued when it has reached the conditions stipulated in religious rules. So that with Zakat it will foster noble character for both muzzaki and mustahiq to uphold the Islamic economy with the grace of Allah Subhanallahu wata'ala. The purpose of this study is to provide empirical evidence that ROA and firm size have an effect on Zakat. This research is quantitative, secondary data using annual financial report data at www.idx.co.id and the company's official website. The sample of Islamic Commercial Bank Companies is 13 Islamic Commercial Banks in 2014-2020 using profitability Return on Assets (ROA) and company size as measured by Ln total assets. This study uses the data testing method used is descriptive statistical analysis, hypothesis testing with SPSS 25 with multiple linear regression data analysis techniques and t test. The results showed that ROA and firm size had a significant effect on corporate zakat.